Effects of Biochar and Compost Applications on Soil Properties and Growth Performance of Amaranthus sp. Grown at Urban Community Garden - Jemima Japakumar; Rosazlin Abdullah; Noor Sharina Mohd Rosli (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Soil quality and fertility deterioration due to the development in urban areas can cause a significant limitation on the yield and sustainability of crops. A field study was done to investigate the effects of biochar and compost application on soil properties and growth performance of Amaranthus sp. grown at urban community garden in Taman Seri Sentosa, Lembah Pantai, Kuala Lumpur. The study was organized using the randomized complete block design (RCBD) with five treatments and four replicates. The treatments are T1 (soil only as a control), T2 (soil+fertilizer), T3 (soil+ fertilizer +biochar), T4 (soil+ fertilizer+compost) and T5 (soil+fertilizer+biochar+compost). In this study, the treatment which consists of both biochar and compost gave the significant increases and highest reading of plant height (50.40 cm), number of leaves (18), plant leaves width (91.61 mm), chlorophyll content (34.3 μmol/m2), plant fresh weight (1.51 kg), dry weight (11.42 g), soil organic matter (10.25%) and soil organic carbon content (5.95%) compared to other treatments. As a conclusion, the combination biochar and compost give the best effects in enhancing the soil properties and growth performance of Amaranthus sp. grown at urban community garden.